Central Bank Digital Currencies: Exploring The Future Of Money And Banking - Petare, Dr. Purushottam Arvind; Josyula, Hari Prasad; Landge, Sunil Rajaram; Gatala, Sudha Kiran Kumar; Gunturu, Srinivasa Rao (Migration Letters, 2024)
As financial landscapes continue to evolve, Central Bank Digital Currencies (CBDCs) have emerged as a focal point in the discourse surrounding the future of money and banking. This review paper delves into the multifaceted dimensions of CBDCs, exploring their implications, challenges, and potential transformative impacts on the global financial ecosystem. By synthesizing a diverse array of academic literature, policy documents, and industry reports, this research aims to provide a comprehensive overview of the current state and future trajectories of CBDCs. The paper begins by delineating the conceptual underpinnings of CBDCs, elucidating [1]the distinctions between retail and wholesale variants, and examining the motivations driving central banks towards their development. It navigates through the technological architectures underpinning CBDCs, assessing the role of blockchain and distributed ledger technologies in enhancing transparency, security, and efficiency within financial transactions. An in-depth analysis of the potential implications and challenges associated with CBDC adoption is presented, encompassing aspects of monetary policy, financial stability, privacy, and the reshaping of traditional banking models. The exploration of cross-border considerations sheds light on the potential for CBDCs to facilitate international transactions and redefine the dynamics of global finance. The review also considers the broader societal impacts, contemplating the democratization of financial services, financial inclusion, and the potential shift in the power dynamics between central banks and commercial banks. Regulatory perspectives and the evolving stance of different nations towards CBDCs are scrutinized to understand the global regulatory landscape surrounding these digital currencies. As CBDCs continue to be piloted and researched by central banks worldwide, this review serves as a timely and insightful resource for policymakers, academics, and industry practitioners seeking a comprehensive understanding of the intricate web of factors surrounding the emergence, adoption, and potential future scenarios of Central Bank Digital Currencies.